Kinetic modeling of methanol synthesis from renewable resources. (16th January 2018) - Seidel, C.; Jörke, A.; Vollbrecht, B.; Seidel-Morgenstern, A.; Kienle, A.
Highlights: New kinetic models for methanol synthesis during chemical energy storage. The models are suitable for strongly fluctuating ratios of CO and CO2 . Parameters are fitted to a large number of steady state and dynamic experiments using global optimization. Identifiability is critically discussed. Abstract: In the present paper new detailed kinetic model for the methanol synthesis from H2, CO2 and/or CO using a Cu/ZnO/Al2 O3 catalyst is proposed. In contrast to most established models different active surface species for CO and CO2 hydrogenation are taken into account. It is shown that changes in the relative amounts of these different surface species, which are related to changes in catalyst morphology, play an important role for the dynamic transient behavior. The model is therefore suitable for evaluating new applications in chemical energy storage, where strongly varying ratios of CO and CO2 are of relevance. The model parameters were fitted to steady state and dynamic experimental data for varying CO/CO2 feed ratios using global optimization. Identifiability is studied using the Profile-Likelihood method giving rise to a reduced kinetic model.